Women development : new approaches and innovations - Sharma, Rashmi Dr. (New Delhi : Regal Publications, 2009)
In Indian context.
Includes bibliographical references (p. [238]-241).
Keywords: Women in development -- Government policy -- India; Women -- Effect of technological innovations on -- India; Rural women -- Effect of technological innovations on -- India; Women -- Education -- India; Women in mass media